Correction: Electrochemical studies on crystalline CuS as an electrode material for non-aqueous Na-ion capacitors. (11th March 2021) - Goswami, Manoj; Nithya, Chandrasekaran; Sathish, N.; Kumar, Satendra; Singh, Netrapal; Srivastava, A. K.; Kumar, Surender
Abstract : Correction for 'Electrochemical studies on crystalline CuS as an electrode material for non-aqueous Na-ion capacitors' by Manoj Goswami et al., New J. Chem., 2020, 44, 5278–5284; DOI: ; 10.1039/C9NJ06465F .